Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Manufaktur - Aprilia Endah Setyo Widodo; Suhendro Suhendro; Purnama Siddi (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to examine and analyze whether there is an effect of financial ratios on stock prices in manufacturing companies. The sample for this survey consists of 30 manufacturing companies with a population of 120 companies. Sampling with a targeted sampling process. The target of this survey is Manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017-2020. The data analysis method used is multiple linear regression analysis which is then processed using SPSS 21 software. The survey results show that the proportion of the Debt to Asset Ratio (DAR) variable has an effect on stock prices with a significance value of 0.000 <0.05. The variable Debt to Equity Ratio (DER) has an effect on stock prices with a significance value of 0.004 <0.05. On the other hand, the Return On Equity (ROE) variable has no effect on stock prices with a significance value of 0.559 > 0.05. The Earning Per Share (EPS) variable has no effect on stock prices with a significance value of 0.651 > 0.05. So for the conclusion of this study resulted that the variables Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) affect stock prices. Meanwhile, the Return On Equity (ROE) and Earning Per Share (EPS) variables have no effect on stock prices.